Sport Injury and Physiotherapy Services in Indonesian Paralympic Athletes at The Asean Paragames in Cambodia 2023 - Adinda Afifah Saharudin; Suryo Saputra Perdana; Retno Setianing; Nur Agung Martopo; Muhammad Tasa Kasumbung; Muhammad Dwiky Anggara; Mega Tia Nurfaiza (UNIB Press, 2025)
The ASEAN Paragames Cambodia 2023 was attended by 268 Indonesian paralympic athletes, the largest number compared to the Tokyo 2020 International Paralympic Games with 23 Indonesian paralympic athletes. Paralympic athletes have a higher prevalence of injuries compared to Olympic athletes. Injuries in paralympic sports vary due to the large percentage of disability. However, there is no literature that specifically describes the frequency and percentage of sports injuries in the categories and areas of sports injuries in the region and physiotherapy services in Indonesian paralympic athletes. The method used was a retrospective descriptive epidemiological study with a cross-sectional approach. This method aims to determine the frequency and percentage of sports injuries in sports categories and affected anatomical areas and types of physiotherapy services in a population at one time without making comparisons or connecting between variables. The sports category of Indonesian Paralympic athletes with the highest number and percentage of injuries was Para Athletics (n=57.35.2%). In the category of the area anatomically affected by the injury, the highest number and percentage was the leg (n=36.22.2%). Physiotherapy services provided to paraathletes with the highest number and percentage was stretching (n=77.19.2%). The high frequency of sports injuries in paralympic athletes indicates that more prevention needs to be done in the future, injuries that occur in paralympic athletes can aggravate existing disabilities and can even interfere with the athlete's ability to carry out daily activities, therefore physiotherapy services are needed to support the handling of injuries in paralympic athletes during competition.